Polityka pieniężna, polityka budżetowa i reformy strukturalne w strefie euro w latach 1999-2006 - Borowiec, Jan (Monetarny Policy, Fiscal Policies and Structural Reforms in the Euro Area, 1999-2006, 2008)
This article aims to assess the ECB's monetary policy, structural reforms in the euro area and fiscal policies of its member states. The analysis of these two fields of macroeconomic policy, namely monetary and fiscal policy, takes into account both: their role in the economic stabilization process and the stability requirements for the common currency. A closer look was taken at labour and product markets reforms, mainly from the point of view of the elasticity of these markets. Since it determines the efficiency of its market adjustments mechanisms, the elasticity of the labour and product markets plays important role in monetary union performance. It can also facilitate pursuing the euro area monetary policy through its transmission mechanisms.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 13-32